Are eSports more than just sitting? A study comparing energy expenditure| - Kocak, U. Z. (Journal of Comparative Effectiveness Research, 2021)
eSports players, who are considered to be physically inactive by sitting, spend approximately 40% more energy than sitting with eSport participation, even at amateur level. According to APM, more energy can be spent in tournaments and at the elite level.